2018
DOI: 10.1515/biol-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects on Seed Germination of 17 Tree Species under Elevated Temperature and CO2 Conditions

Abstract: Effects on seed germination characteristics of 17 tree species were investigated under elevated temperature and CO2. Seeds of 5 needle-leaf and 12 broad-leaf species were germinated under four conditions: 24°C + 400 μmol CO2 mol air–1, 24°C + 750 μmol CO2 mol air–1, 27°C + 400 μmol CO2 mol air–1, and 27°C + 750 μmol CO2 mol air–1. The elevated temperature and CO2 affected germination percent (GP) of 7 tree species seeds.GPs of Pinus densiflora, P. thunbergii, Betula ermanii, and Maackia amurensisseeds were aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Temperature is widely known as one of the most important environmental factors regulating seed dormancy and germination [12]. Previous studies reported that the optimal temperature requirement for germination is species-specific [54,55]. Such patterns have been described for different ecosystems worldwide, including Arabian deserts [56], Mediterranean systems [57] and tropical forests [58].…”
Section: Discussionmentioning
confidence: 98%
“…Temperature is widely known as one of the most important environmental factors regulating seed dormancy and germination [12]. Previous studies reported that the optimal temperature requirement for germination is species-specific [54,55]. Such patterns have been described for different ecosystems worldwide, including Arabian deserts [56], Mediterranean systems [57] and tropical forests [58].…”
Section: Discussionmentioning
confidence: 98%
“…ex Endl., showed the maximum seed germination (90%) at 15 or 20 0 C with or without light, whereas at 25-30 0 C, there was a reduction in the seed germination as well as the emergence of the radicle was also delayed (12). Similar studies conducted on Pinus densiflora, P. thunbergii and Maackia amurensis showed that high temperature not only reduced percent germination but also delay it, representing that seed germination of Pinus species is highly sensitive to high temperature (13,14).…”
Section: Impact On Seed Germinationmentioning
confidence: 63%
“…Moreover, [25] mention that CO 2 concentration did not have a significant effect on Arabidopsis thaliana seed emergence, with seeds subjected to high temperatures exhibiting the fastest germination rate. In the present work, temperature was essential in the regulation of seed emergence; when the temperature increased, so did the emergence rate, due to temperature acting as a determining factor for enzyme activation or deactivation processes [26,27]. The physiological response of seeds to this factor is crucial for emergence and plant development, and once the optimum temperature point is reached, the emergence process diminishes.…”
Section: Seedling Emergencementioning
confidence: 67%